PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES MENGGUNAKAN LKS TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMAN I SUTERA KABUPATEN PESISIR SELATAN - Fitri Rahmadani; Syafri Anwar; nofrion dion (JURNAL BUANA, 2017)
The purpose of the research to determine the effect of the application of active learning type of Hollywood Squares using LKS to the results of learning geography students class XI IPS SMAN 1 Sutera Pesisir Selatan Regency. The hypothesis in this study is "There is a significant influence on the application of active learning of the type of Hollywood Squares using LKS to the students' geography result of grade XI SMAN 1 Sutera Pesisir Selatan Regency". This type of research is quasi-experimental, with randomized control only design. The population in this study were students of class XI IPS SMAN 1 Sutera Pesisir Selatan Regency enrolled in the 2016/2017 academic year, selected sample using cluster random sampling technique, which selected XI IPS2 class as control class and class XI IPS1 as experiment class. To test the hypothesis used two equality test (t) at the 0.05 level.The result of the data analysis shows that the experimental class has an average value of cognitive domain of 81.25 while the control class has a mean of cognitive domain of 73.88. The calculation of the cognitive sphere t obtained (95) (62) is 1.66. Thus the hypothesis presented earlier can be accepted at 95% confidence level. Based on this it can be concluded that the application of active learning type Hollywood Squares using LKS can improve learning outcomes geography class XI IPS SMAN 1 Sutera Pesisir Selatan Regency.